Analisis Karakteristik Arus Lalu Lintas Dengan Model Greenshield, Greenberg dan Underwood di Ruas Jalan Kota Pekanbaru (Studi Kasus Jalan Hr. Soebrantas KM. 9,5 Kota Pekanbaru) - Athallah, Afif; Rhoma Putra, Benny Hamdi; Djuniati, Sri (SAINSTEK, 2024)
Traffic congestion on HR Soebrantas Street in Pekanbaru has become a serious issue. This provincial road, serving as a 4/2D collector road, connects Pekanbaru City and Kampar Regency. The u-turn at KM 9.5, in front of BANK BCA Panam, is the focus of the study. Utilizing MKJI 1997 and Regression Analysis (Greenshield, Greenberg, Underwood models), the highest coefficient of determination occurred on June 24, 2023, with an R2 of 0.973. In the Underwood model, the relationships (U-D): U = 43.403 x e-D/162.275, (V-D): V = D x 43.403 x e-D/162.275, (V-U): V = Us x 162.275 x Ln (43.403/Us). Maximum volume is 2,591,078 pcu/hour, maximum density is 162,275 pcu/km, maximum speed is 15,967 km/h, and free flow speed is 43,403 km/h. According to MKJI, the capacity (C) is 3,312,910 pcu/hour, with a Level Of Service of F (DS = 1,685), indicating characteristics of congested and stalled traffic.